Α-spectrum estimation for 1/f processes in noisy environments. (February 2019) - Wang, Chen; Shi, Yao-Wu; Zhu, Lan-Xiang; Deng, Li-Fei; Shi, Yi-Ran; Wang, De-Min
In the past, 1/ f noise was regarded as a stochastic process that accords with Gaussian distribution. According to our studies, the output transistor 1/ f noise can be characterized more accurately as non-Gaussian α -stable distribution rather than Gaussian distribution. We define and consistently estimate the samples normalized cross-correlations of linear S α S processes and propose a samples normalized cross-correlations–based α -spectrum method effective in noisy environments. Simulation results and diodes noise spectrum estimation results exhibit good performance.